Stenting of Anomalous Left Main Coronary Artery Stenosis in an Adult with a Retroaortic Course - Lanjewar Charan; Santosh Shiradkar; P. G. Kerkar; Agrawal Ashish (Cardiology Research and Practice)
Coronary bypass graft has been the conventional treatment of choice in anomalous left man coronary artery stenosis. We are reporting an interesting case with anomalous left main coronary artery originating from right aortic sinus having retroaortic course complicated by significant atherosclerotic narrowing of the vessel and its percutaneous management.